School refusal behaviour: Are children and adolescents with autism spectrum disorder at a higher risk?. (September 2017) - Munkhaugen, Ellen Kathrine; Gjevik, Elen; Pripp, Are Hugo; Sponheim, Eili; Diseth, Trond H.
Highlights: School refusal behavior (SRB) is pervasive in students with ASD, aged 9–16 years. SRB is equally common in primary and secondary students with ASD. Expressions of SRB differ between primary and secondary school students with ASD. Illness of other family members is associated to SRB in students with ASD. Abstract: School refusal behaviour in students with autism spectrum disorder (ASD) is poorly studied despite being considered a serious problem. This study assessed the frequency, duration, and expression of school refusal behaviour in students with ASD, aged 9–16 years, without intellectual disability. Further, the associations between school refusal behaviour and sociodemographic factors were explored. Teachers and parents assessed this behaviour over 20 days in a cross-sectional study of 216 students, including 78 students with ASD and 138 typically developing (TD) students. School refusal behaviour was significantly higher in students with ASD as compared to TD students. Significant associations were found between school refusal behaviour and illness of other family members. The study concludes that school refusal behaviour is pervasive in students with ASD.